Chapter Il filo da riannodare: Massimo Quaini, una letteratura per la geografia e una geografia per la letteratura - Gabellieri, Nicola (Territori, 2021)
With regard to the relationship between literary works and geographical studies, Massimo Quaini's interest consolidated into a heuristic imprint whose originality has not yet been adequately enlightened. Through the analysis of his essays, the paper identifies some clues of his thought: methodologically, the need for a critical approach of 'archeology of knowledge and sources' to the writer's profile; teleologically, the identification of the geographical factors inside the works as a tool for territorial enhancement; epistemologically, the use of literary topoi and metaphors as an interpretive key - together with the geographical-historical analysis - of the historical and current territorial dynamics.